Knowledge and practice of radiation protection among medical professionals in interventional radiology at private hospitals in Ipoh - Ramli, Nabilah; Nor Azman, Nurul Dizyana; Supar, Rafidah (Faculty of Medicine, 2026)
The increasing use of interventional radiology (IR) procedures has raised concerns on radiation exposure awareness among medical professionals (MPs) in hospitals. The aim was to determine association between knowledge and practice score with MPs demographic data in IR procedures at private hospitals in Ipoh, Perak. Methods: A cross-sectional study was conducted in two private hospitals in Ipoh, Perak, involving 90 medical professionals including specialists, radiographers, and nurses. The questionnaire consists of three sections which are demographic, knowledge and practice of radiation protection and was shared online through Google Forms. Data were analysed using the Pearson chi-square test, with a significance level of p < .05. Results: The results indicated that statistically significant and strong association between knowledge and radiation training, χ² (2, N=90) 44.950, p <.001 but not statistically significant between practice and radiation training, χ² (2, N=90) = 5.254, p = .072. Level of education also shown statistically significant and strong association for knowledge χ² (2, N=90) 24.18, p <.001 as well as practice, χ² (2, N=90) 30.49, p <. 001.Conclusions: These results show that participation in radiation training is factor to improve knowledge in radiation protection. Level education is also a contributing score for radiation protection where the entry level of education for radiographers and nurses is diploma while specialist is up to master’s degree. This result emphasizes a need for regular radiation training for MPs to update and improve knowledge and application in any procedure involving ionising radiation.